Electrostatic Field Enhanced Photocatalytic CO2 Conversion on BiVO4 Nanowires - Yue, Shuai; Chen, Lu; Zhang, Manke; Liu, Zhe; Chen, Tao; Xie, Mingzheng; Cao, Zhen; Han, Weihua (Nano-Micro Letters, 2021)
The recombination loss of photo-carriers in photocatalytic systems fatally determines the energy conversion efficiency of photocatalysts. In this work, an electrostatic field was used to inhibit the recombination of photo-carriers in photocatalysts by separating photo-holes and photo-electrons in space. As a model structure, (010) facet-exposed BiVO4 nanowires were grown on PDMS-insulated piezo-substrate of piezoelectric transducer (PZT). The PZT substrate will generate an electrostatic field under a certain stress, and the photocatalytic behavior of BiVO4 nanowires is influenced by the electrostatic field. Our results showed that the photocatalytic performance of the BiVO4 nanowires in CO2 reduction in the negative electrostatic field is enhanced to 5.5-fold of that without electrostatic field. Moreover, the concentration of methane in the products was raised from 29% to 64%. The enhanced CO2 reduction efficiency is mainly attributed to the inhibited recombination loss of photo-carriers in the BiVO4 nanowires. The increased energy of photo-carriers and the enhanced surface absorption to polar molecules, which are CO in this case, were also play important roles in improving the photocatalytic activity of the photocatalyst and product selectivity. This work proposed an effective strategy to improve photo-carriers separation/transfer dynamics in the photocatalytic systems, which will also be a favorable reference for photovoltaic and photodetecting devices. Highlights: 1 BiVO4 nanowires with exposed (010) facets were deposited on the piezoelectric transducer piezo-substrate. 2 CO2 conversion rate was significantly improved by 5.5-time in an electrostatic field generated by applying a stress on the piezo-substrate. 3 The mole percentage of methane in products was increased from 29% to 64%. 4 The improved performance was attributed to the facilitated photo-carriers separation/transfer, as well as the enhanced adsorption of polar molecules.